I have an equation that is a = d/b + d/c . Supposedly this means that
d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?
Someone told me to factor out d first but I'm not sure how. Thanks.
gcmky wrote:I have an equation that is a = d/b + d/c . Supposedly this means that
d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?
Someone told me to factor out d first but I'm not sure how. Thanks.
stapel_eliz wrote:gcmky wrote:I have an equation that is a = d/b + d/c . Supposedly this means that
d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?
Someone told me to factor out d first but I'm not sure how. Thanks.
If you had "db + dc", would you be able to factor?
gcmky wrote:Think I got it. Thanks.
a = d/b + d/c
a = d(1/b) + d(1/c)
a = d(1/b + 1/c)
a/(1/b + 1/c) = d(1/b + 1/c) / (1/b + 1/c)
a/(1/b + 1/c) = d